Remarks on the Dynamics of a DC Motor Moving a Cart Horizontally - Avanço, Rafael Henrique; Zanella, Danilo Antonio; de Jesus Arias Cantillo, Raibel; Cunha, Américo; Balthazar, José Manoel [UNESP]; Tusset, Angelo Marcelo (Springer Nature, 2024)
The present text analyzes the dynamics of a DC motor coupled to a cart moved horizontally with a yoke scotch mechanism. The common concept about the inductance in DC motors is the influence in the transient region. The start in DC motors depend on the current and the inductance, but when it reaches a steady state the influence of the inductance diminishes and the current approaches to a mean value determined by the voltage set and the speed of the motor. However, when the motor speed fluctuates, the current may not be a constant and the inductance maybe needs to be considered. The results in the present analysis use different values for the mass moved by the yoke scotch, what causes a variable load acting over the DC motor provoking fluctuations on the speed. The conclusion is that in some specific cases it is necessary to consider the inductance of DC motors but in most of cases the inductance may be neglected without loss in the numerical results.
Keywords: Cart; DC motor; Inductance; Yoke scotch